Description of Sleep Quality among Final Year Nursing Students in Denpasar City - Ida Ayu Bunga Udiyani; Putu Intan Daryaswanti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Final year nursing students tend to have a busy academic schedule and academic demands to complete their final assignments, which can lead to fatigue and stress, potentially causing sleep quality disturbances. Sleep quality is defined as an individual's satisfaction with their sleep, wherein they do not exhibit symptoms of sleep deprivation or difficulty sleeping. This study aims to describe the sleep quality of final year nursing students in Denpasar City. This descriptive study used a quantitative approach with the Pittsburgh Sleep Quality Index (PSQI) as an instrument and a simple random sampling technique, with a sample of 220 respondents being final year nursing students in Denpasar City. Most final year nursing students in Denpasar City were 22 years old (49.5%), female (95%), and (59.1%) of respondents did not have a habit of drinking coffee or tea. A total of (78.6%) of respondents had poor sleep quality. About (65%) of respondents reported insufficient sleep in the past month, (62.7%) had difficulty falling asleep within 16-30 minutes, (78.9%) had a sleep duration of 6-7 hours per day, (87.3%) had a sleep efficiency >85%, (91.8%) had nighttime sleep disturbances with a score between 1-9, (99.5%) did not use sleeping pills in the past month, and (59.5%) often felt sleepy during the day. The poor sleep quality among final year nursing students can be attributed to academic demands to complete final assignments and the habit of staying up late. Therefore, students are expected to manage their sleep patterns better.